Microeconomics - Samuelson, Paul A.; Nordhaus, William D. (Boston, Massachusetts : McGraw Hill Education, 2010)
Suitable for principles of economics courses, this book offers an introduction to modern economics principles.
Basic concepts -- Microeconomics : supply, demand and product markets -- Factor markets : labor, land and capital -- Applications of economic principles
Includes index.
Keywords: MICROECONOMICS